Effects of a myostatin mutation in Japanese quail (Coturnix japonica) on the physicochemical and histochemical characteristics of the pectoralis major muscle - Kim, Dong-Hwan; Lee, Boin; Lee, Joonbum; Bohrer, Benjamin M.; Choi, Young Min; Lee, Kichoon (Frontiers in Physiology, 2023)
The aim of this study was to compare the carcass, meat quality, and histochemical characteristics of pectoralis major (PM) muscle between wild type (WT) and myostatin (Mstn) homozygous mutant (HO) quail lines. The HO quail line exhibited significantly heavier body weight (HO vs. WT, 115.7 g vs. 106.2 g, approximately 110%) and PM muscle weight (HO vs. WT, 18.0 g vs. 15.2 g, approximately 120%) compared to the WT (p < 0.001). However, the two groups had similar traits (pH, redness, yellowness, and drip loss) for meat quality, although slightly higher lightness and cooking loss were observed in the mutant quail (103% and 141%, respectively, p < 0.05). For histochemical traits of PM muscle, Mstn mutant quail exhibited lower type IIA and higher type IIB percentage in the deep region than WT quail (p < 0.05), indicating a fiber conversion from the type IIA to IIB. However, the two quail lines had comparable histochemical traits in the superficial region (p > 0.05). These data suggest that Mstn mutation greatly increases muscle mass without significantly affecting meat quality.